Shari'ah governance framework of Islamic banking in Oman - Alnofli, Abdulrahman (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2020)
Shari'ah compliance is the backbone for the activities and governance of Islamic banking and finance. IFIs are required to ensure sound Sharī'ah governance to achieve their target in ensuring a solid Shari'ah compliance mechanism. Oman adopted a Shariah governance framework that is very similar with other countries such as Malaysia, Pakistan, and Bahrain. Therefore, there is a very high potential that the same issues of Shariah governance apply to in Oman too. This study aims to examine the current practice of Shari'ah governance in Oman from the perspectives of Shari'ah advisors, bankers and regulators. The study focuses on the present practice of Shari'ah governance framework and related issues such as independence, competency and disclosure. The study used descriptive research method in terms of collecting secondary data and information for the literature review. Since the availability of data and information on Shari'ah governance practices in Oman is very limited, a semi-structured interview was conducted with Shari'ah advisors, officers and regulators to explore their perceptions on Sharī'ah governance and related issues. The findings of the study reveal that the regulators have put in place an excellent Sharī'ah governance framework and it is considered one of the best frameworks in Islamic banking industry. However, there are shortcomings and weaknesses in the current practice of Sharī'ah governance framework such as lack of experience, lack of research in the field of Islamic banking and finance and low position of internal Shari'ah review. The study suggests that Intensive training should be organized by the CBO for the Omani members of SSB in the field of Islamic banking and finance.